Media Promosi Berbentuk Video Series Pada MNC Vision Pictures - Mohamad Ifran Sanni; Deddy Rusdiansyah; Po Abas Sunarya (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2023)
In the current era of globalization, the media is a very effective means of communication in conveying a message in the form of information or a promotion. Information that is easily obtained from anywhere, be it via the internet or print media such as magazines. Schools as educational institutions also require means of information and promotion. Especially private companies such as MNC Vision Pictures. The purpose of this study is to improve the public to be more familiar with the events in Vision +. Currently, information activities carried out in activities to convey information and promotions that previously only used brochure media, which were considered still simple and incomplete in providing information about Vision + shows, movie shows, entertainment, talk shows and various activities in Vision +, so that visual communication media in the form of curls is needed that can help Vision + in informing and promoting MNC Vision Pictures. The research methods used are data collection, namely observation, interviews, literature studies, design concept methods, media design and SWOT analysis. This promotional advertising media is designed using Adobe Premiere Pro CC 2019, Adobe Photoshop CC 2019 software. The result of this study is the design of visual communication media in the form of advertisements. Keywords—Media, Promotion, Advertisements Dizaman era globalisasi saat ini media menjadi sarana komunikasi yang sangat efektif dalam menyampaikan sebuah pesan berupa informasi maunpun sebuah promosi. Informasi yang dengan mudah didapatkan dari mana saja baik itu via internet ataupun media cetak seperti majalah. Sekolah sebagai lembaga pendidikan juga memerlukan sarana informasi dan promosi. Terutama perusahaan swasta seperti MNC Vision Pictures. Tujuan dari penelitian ini adalah untuk meningkatkan masyarakat lebih mengenal acara-acara yang ada di Vision +. Saat ini kegiatan informasi yang dilakukan dalam kegiatan menyampaikan informasi dan promosi yang sebelumnya hanya menggunakan media brosur saja, yang dinilai masih sederhana serta kurang lengkap dalam memberikan informasi mengenai tayangan Vision +, tayangan film,hiburan,talkshow dan berbagai kegiatan yang ada di Vision +, sehingga dibutuhkan media komunikasi visual berupa ikaln yang dapat membantu Vision + dalam menginformasikan dan mempromosikan MNC Vision Pictures. Adapun metode penelitian yang digunakan yaitu pengumpulan data yaitu observasi, wawancara, studi pustaka, metode konsep desain, perancangan media dan analisis SWOT. Media iklan promosi ini dirancang menggunakan software Adobe Premiere Pro CC 2019, Adobe Photoshop CC 2019. Hasil dari penelitian ini adalah perancangan media komunikasi visual yang berbentuk iklan. Kata Kunci—Media, Promosi, Advertisement